2021
DOI: 10.46347/jmsh.2021.v07i01.013
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Evaluate Use of Platelet Indices in Hyperdestructive Thrombocytopenia: A Two-year Experience from Tertiary Care Rural Hospital

Abstract: Background: Thrombocytopenia is one of the most common causes of abnormal bleeding and is defined as platelet counts < 1.5 lakhs/cumm. Three processes can cause thrombocytopenia, namely: Deficient platelet production, accelerated platelet destruction, and abnormal pooling of the platelets within the body. Of these, accelerated platelet destruction is the most common cause for thrombocytopenia and has variety of etiologies. The usefulness of bone marrow analysis in assessing accelerated platelet destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Mittal V et al [10] did a study on patients aged 1 to 80 years old and found that 65 percent of the patients were male and 35 percent were female. Francis et al [11] found 61.2% male and 38.8% female patients, with a male to female ratio of 1.57:1. Grade 1 thrombocytopenia is most frequent (47%) followed by grade 2 (24%), grade 3 (15.0%) and grade 4 (14%).…”
Section: Discussionmentioning
confidence: 95%
“…Mittal V et al [10] did a study on patients aged 1 to 80 years old and found that 65 percent of the patients were male and 35 percent were female. Francis et al [11] found 61.2% male and 38.8% female patients, with a male to female ratio of 1.57:1. Grade 1 thrombocytopenia is most frequent (47%) followed by grade 2 (24%), grade 3 (15.0%) and grade 4 (14%).…”
Section: Discussionmentioning
confidence: 95%